Recent advances in biodegradable nanocomposites - Pandey, J. K.; Kumar, A. P.; Misra, M.; Mohanty, A. K.; Drzal, L. T.; Singh, R. P. (Journal of Nanoscience and Nanotechnology, 2005)
There is growing interest in developing bio-based products and innovative process technologies that can reduce the dependence on fossil fuel and move to a sustainable materials basis. Biodegradable bio-based nanocomposites are the next generation of materials for the future. Renewable resource-based biodegradable polymers including cellulosic plastic (plastic made from wood), corn-derived plastics, and polyhydroxyalkanoates (plastics made from bacterial sources) are some of the potential biopolymers which, in combination with nanoclay reinforcement, can produce nanocomposites for a variety of applications. Nanocomposites of this category are expected to possess improved strength and stiffness with little sacrifice of toughness, reduced gas/water vapor permeability, a lower coefficient of thermal expansion, and an increased heat deflection temperature, opening an opportunity for the use of new, high performance, lightweight green nanocomposite materials to replace conventional petroleum-based composites. The present review addresses this green material, including its technical difficulties and their solutions.
Keywords: cellulose; layered silicates and properties; Nanocomposite; poly(caprolactone)s; poly(hydroxy alkanoate)s; polyiactic acid; Starch